Willful Liberalism : Voluntarism and Individuality in Political Theory and Practice - Flathman, Richard E. (Book collections on Project MUSE., 1992)
In this book Richard E. Flathman argues vigorously for a new understanding of the proper place of voluntarism, individuality, and plurality in the political and moral theory of liberalism. Giving close and sympathetic attention to thinkers who are seldom considered in debates about liberalism, he draws upon thinking within and outside the liberal canon to articulate a refashioned liberalism that gives a more secure prominence to plurality and a robust individuality. Flathman focuses on political philosophers whose work deals with willfulness and the will in human practice. He is concerned with the thinking of such nominalist medieval theologians as John Duns Scotus and William of Ockham; of Hobbes; and of Arthur Schopenhauer, Friedrich Nietzsche, and William James. He also explores the writings of such contemporary philosophical psychologists as Brian O'Shaughnessy and, in particular, Wittgenstein, and of such twentiethcentury political theorists as Isaiah Berlin, John Rawls, Hannah Arendt, and especially Michael Oakeshott. Appropriating ideas from widely disapproved thinkers and from theological sources commonly thought to be incompatible with liberalism, he formulates what is in many ways a strongly personal statement, one that is unorthodox and potentially disturbing. Sharply controversial, Willful Liberalism is certain to enliven and invigorate political and moral debate, and it may well help to revive liberalism as the dominant public philosophy of our culture, setting it on a new and better course.